Analisis Pemanfaatan Portalsia sebagai Sistem Informasi Akademik di UIN Sumatera Utara - Dwi Artika Urbasari; Fahrinsal Sitorus; Nurbaiti Nurbaiti (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
Digital transformation in education encourages universities to utilize adaptive and responsive academic information systems. This study aims to evaluate the utilization of the Portalsia academic information system at the State Islamic University of North Sumatra (UINSU) based on the experience of students as the main users. A qualitative descriptive approach was used with data collection techniques through semi-structured interviews with 15 students from various study programs. The results of the study show that Portalsia has been utilized in various academic activities, such as filling in KRS, checking grades, and printing KHS. However, there are still a number of obstacles, such as low system stability during peak usage, a less intuitive interface, and minimal training and socialization for users. This study recommends increasing server capacity, developing interface designs based on user experience (UX) principles, regular training for students, and is expected to be a reference for the development of a more adaptive academic information system and the process of digitalizing academic services in universities.